2010
DOI: 10.4028/www.scientific.net/amr.163-167.3701
|View full text |Cite
|
Sign up to set email alerts
|

Friction Loss of Externally Prestressed Concrete Beams with Carbon Fiber-Reinforced Polymer Tendons

Abstract: Friction loss is an important component of the calculation of prestressing loss for external prestress strengthening technology. Unfortunately, the test data of relevant curvature friction and wobble coefficients is scarce, especially for beams strengthened by external prestressing Carbon Fiber-Reinforced Polymer (CFRP) tendons. Through the experiment of 12 concrete beams strengthened by external prestressing CFRP tendons, this study attempts to discuss the friction loss algorithm and the reasonable value of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In order to investigate the effect of friction on strain increment, a relatively conservative value of j = 0.0015/m for wobble friction and g = 0.264/rad. provided by Yu and Zhang (2011) were used. It was found that only a marginal difference of 1 % (5 %) for total strain (strain increment) was observed due to frictional loss.…”
Section: Modified Algorithm To Include Frictional Lossesmentioning
confidence: 99%
“…In order to investigate the effect of friction on strain increment, a relatively conservative value of j = 0.0015/m for wobble friction and g = 0.264/rad. provided by Yu and Zhang (2011) were used. It was found that only a marginal difference of 1 % (5 %) for total strain (strain increment) was observed due to frictional loss.…”
Section: Modified Algorithm To Include Frictional Lossesmentioning
confidence: 99%
“…CLS concrete with large elastic modulus is sensitive to the increase in concrete age, and the creep and shrinkage is more obvious than normal concrete [2]. When compared with long-term pre-stress loss [5][6][7][8], the instantaneous loss caused by friction also significantly affects the initial pre-stress force of the tendon [10][11][12][13][14][15]. The effective force inevitably decreases due to the friction loss between the pre-stressing tendon and duct [10].…”
Section: Introductionmentioning
confidence: 99%